TDMA Device Identification Using Continuity of Carrier Phase. (May 2019) - Pan, Y; Peng, H; Li, T; Wang, W
Abstract: Specific emitter identification provides the capability to distinguish radio emitters with the external features carried by the received waveforms. As existing features are not specific to time-division multiple access (TDMA) devices, it is yet intractable to discern the emitter in the case of low signal-to-noise rates or short durations. In this paper, we propose a novel characteristic based on the continuity of carrier phase and explore its application on TDMA device identification. The characteristic reflects a fact whether adjacent time slots are assigned to the same user terminal, which reveals a potential link between slots even if the protocol is unknown. To apply it to TDMA device identification, we augment the typical SEI scheme with two subsystems, Decision and Correction, in which the recognition results can be corrected to improve the accuracy. Simulation results demonstrate that the characteristic is resilient against the ambient noise, and it evidently improves the recognition accuracy.